2021
DOI: 10.1093/geroni/igab046.064
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Activities, Emotions, and Pleasant Events and Their Associations With Mental and Cognitive Health

Abstract: The COVID-19 pandemic dramatically changed the structure of our daily lives. One of the most significant changes is a limited opportunity to engage in face-to-face social interactions and enjoy diverse daily activities. This raises a public health concern, because diverse experiences are critical sources of health by increasing social integration, cognitive reserve, and psychological resources. Recently, two lines of research have consistently shown that activity diversity or emodiversity is associated with mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Importantly, quantitative evidence investigating the positivity effect links behavior, as revealed through language use, to psychosocial variables such as emotional stability (Schwartz et al, 2013) and emotional diversity, echoing similar work connecting frequent use of positive words to positive emotion states (Kern et al, 2016) in both young (Quoidbach et al, 2014;Rivera-Hernandez et al, 2021) and midlife adults (Urban-Wojcik et al, 2022). Therefore, utilizing the Think-Aloud Paradigm and extracting affective vocabularies from its resultant linguistic content, we can assess whether the positivity effect persists in the resting state thought of older adults.…”
Section: Introductionmentioning
confidence: 79%
“…Importantly, quantitative evidence investigating the positivity effect links behavior, as revealed through language use, to psychosocial variables such as emotional stability (Schwartz et al, 2013) and emotional diversity, echoing similar work connecting frequent use of positive words to positive emotion states (Kern et al, 2016) in both young (Quoidbach et al, 2014;Rivera-Hernandez et al, 2021) and midlife adults (Urban-Wojcik et al, 2022). Therefore, utilizing the Think-Aloud Paradigm and extracting affective vocabularies from its resultant linguistic content, we can assess whether the positivity effect persists in the resting state thought of older adults.…”
Section: Introductionmentioning
confidence: 79%
“…Some studies have found that with increasing age, individuals use more positive (compared to negative) affective words and use fewer references to the self (Pennebaker & Stone, 2003). Importantly, quantitative evidence links language use to psychosocial variables such as personality and emotional stability (Schwartz et al, 2013), echoing similar work connecting frequent use of positive words to positive emotion states (Kern et al, 2016) in both young (Quoidbach et al, 2014;Rivera-Hernandez et al, 2021) and midlife adults (Urban-Wojcik et al, 2022). According to the socioemotional selectivity theory, a shift toward positive stimuli over the lifespan can be explained by a change in motivation and goals as time horizons become increasingly constrained (Carstensen et al, 1999).…”
mentioning
confidence: 98%